2014
DOI: 10.1007/s11250-014-0686-2
|View full text |Cite
|
Sign up to set email alerts
|

Fertility subindex for improving fertility performance in Iranian Holstein cows

Abstract: Different fertility indices were constructed for improving fertility performance in Iranian Holstein dairy cows. Number of inseminations per conception and days from calving to first insemination, each weighted by its economic value, were included as breeding goals in the aggregate genotype definition. Different fertility indices (FI) were constructed with different combinations of available fertility traits: number of inseminations to conception (INS), days from calving to first service (DFS), interval betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The positive signs for production traits and negative sign for functionality trait mean that the index developed will allow breeders to select sires and dams, which will increas the production traits and decrease the functionality trait. Ghiasi et al (2015) reported that the fertility sub index which includes DO (I= 1.69*DO) had the highest correlated genetic gain for number of inseminations to conception (−0.25 time/ generation), and days from calving to first service (−8.6 day/generation). Therefore, this index had the highest profit per US dollar (3.5 US dollar /generation), among the other selection indices.…”
Section: Selection Index and The Expected Genetic Gainmentioning
confidence: 99%
“…The positive signs for production traits and negative sign for functionality trait mean that the index developed will allow breeders to select sires and dams, which will increas the production traits and decrease the functionality trait. Ghiasi et al (2015) reported that the fertility sub index which includes DO (I= 1.69*DO) had the highest correlated genetic gain for number of inseminations to conception (−0.25 time/ generation), and days from calving to first service (−8.6 day/generation). Therefore, this index had the highest profit per US dollar (3.5 US dollar /generation), among the other selection indices.…”
Section: Selection Index and The Expected Genetic Gainmentioning
confidence: 99%